2022
DOI: 10.1111/asap.12306
|View full text |Cite
|
Sign up to set email alerts
|

Individual values and career choice: Does cultural context condition the relationship?

Abstract: This paper explores how the individual values of self‐direction, power, and benevolence predict career decisions (self‐ or paid employment). By observing heterogeneity in career patterns across countries, this research examines the moderating effect of cultural contexts (gender egalitarianism, performance orientation, and collectivism) on this relationship. Blending the theory of human values (THVs) and institutional theory (IT), we test hypotheses using the World Values Survey (WVS) Wave 6 data and GLOBE cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 97 publications
0
1
0
Order By: Relevance
“…Available studies on entrepreneurship have demonstrated the importance of work values in inducing entrepreneurship and the success of entrepreneurial ventures. Work values are dynamic and are influenced by personal experiences, cultural norms, and access to new information (Ayob et al ., 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Available studies on entrepreneurship have demonstrated the importance of work values in inducing entrepreneurship and the success of entrepreneurial ventures. Work values are dynamic and are influenced by personal experiences, cultural norms, and access to new information (Ayob et al ., 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…No contexto educacional, estudantes com atitudes positivas frente ao processo de aprendizagem se envolvem mais nas atividades acadêmicas e obtêm melhor desempenho acadêmico (Attard, 2012). Nessa direção, quando o sentimento dos alunos sobre a utilidade do conteúdo é positivo e eles se sentem confortáveis com a disciplina, gostam mais de aprender, estabelecem metas específicas de aprendizagem, com o objetivo de adquirir novos conhecimentos e buscam um excelente desempenho escolar (Sanchal & Sharma, 2017).…”
unclassified